2019
DOI: 10.4274/balkanmedj.galenos.2019.2019.4.88
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Echocardiographic Epicardial Adipose Tissue Thickness on Success Rates of Premature Ventricular Contraction Ablation

Abstract: Background:Idiopathic premature ventricular contractions are frequently detected ventricular arrhythmias, and radiofrequency ablation is an effectively treatment for improving symptoms and eliminating premature ventricular contractions. Studies have reported a relationship between an elevated epicardial adipose tissue thickness and myocardial structural pathologies. However, the association between epicardial adipose tissue thickness and success rates of premature ventricular contraction ablation has not yet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…All these changes may predispose the heart to arrhythmias such as ventricular extra-systoles. 6,23 However, much uncertainty still exists about the relation between EFT thickness and PVCs. Surveys such as that conducted by Nabati et al have shown a significant association between increased EFT thickness and some cardiovascular risk factors, including calcium deposits in the mitral valve annulus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All these changes may predispose the heart to arrhythmias such as ventricular extra-systoles. 6,23 However, much uncertainty still exists about the relation between EFT thickness and PVCs. Surveys such as that conducted by Nabati et al have shown a significant association between increased EFT thickness and some cardiovascular risk factors, including calcium deposits in the mitral valve annulus.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 The amounts of PVC attacks of more than 10-25% of total heart beats in a day have been reported to be associated with decreased ventricular function, ventricular dilation, and increased risk of cardiomyopathy. 2,6 Related risk factors and etiology of PVC are not fully known in patients with normal heart structure. However, some cardiac disorders such as ischemia, myocardial hypertrophy, cardiomyopathy and chronic heart failure have been reported to be potential predisposing factors in developing frequent PVCs in patients suffering from structural heart diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, EAT was an independent marker of impaired heart rate recovery, a noninvasive index of autonomic nerve dysfunction in obese patients with obstructive sleep apnea, portending poor cardiovascular prognosis in obese patients [ 119 ]. Finally, echocardiography-derived EAT thickness was higher in patients with premature ventricular contraction ablation failure [ 120 ].…”
Section: Cardiac Adiposity and Ventricular Arrhythmiasmentioning
confidence: 99%
“…1,2,6 Frequent PVCs are defined as attacks of >10%-25% of the total number of heartbeats detected by 24-hour rhythm Holter monitoring. 7 The related risk factors are not entirely known yet, but some structural heart diseases such as ischaemia, myocardial hypertrophy, cardiomyopathy and chronic heart failure have been noted to be in association with PVCs; therefore, patients with more frequent PVCs should undergo meticulous evaluation of underlying heart diseases as frequent PVCs can be contributed to increased mortality rate because of arrhythmia-induced cardiomyopathy. 2,8,9 Further, several studies have demonstrated that PVCs have a considerable impact on increasing the risk of cardiovascular adverse effects, including left ventricular systolic and diastolic dysfunction in addition to decreased cardiac capacity, serious events related to arrhythmia (eg, ventricular fibrillation or ventricular tachycardia), myocardial infarction (MI) and ischaemic stroke.…”
Section: Backg Rou N Dmentioning
confidence: 99%